A systematic review and network meta-analysis of neoadjuvant therapy combined with surgery for patients with resectable esophageal squamous cell carcinoma. (February 2017) - Huang, Yuanwei; Wang, Haidong; Luo, Ganfeng; Zhang, Yanting; Wang, Li; Li, Ke
Abstract: Background: The role of neoadjuvant therapy combined with surgery for treating esophageal squamous cell carcinoma (ESCC) remains controversial. We performed a network meta-analysis to synthesize direct and indirect evidence to identify the optimal therapeutic method for ESCC. Methods: We identified 15 randomized controlled trials that compared any of the following 4 therapeutic measures: surgery alone (S), preoperative chemotherapy followed by surgery (CTS), preoperative radiotherapy followed by surgery (RTS), and preoperative chemoradiotherapy followed by surgery (CRTS). The main outcomes were 5-year survival, rate of radical resection, operative mortality and postoperative complications. Results: Network meta-analysis showed that CRTS was associated with improved survival as compared with S (OR = 1.50 [95% CI 1.21 to 1.97]) and decreased occurrence of complications as compared with RTS (OR = 0.50 [95% CI 0.22 to 0.99]). Direct evidence revealed CRTS associated with improved survival (OR = 1.61 [95% CI 1.01 to 2.57]) and radical resection (OR = 4.01 [95% CI 1.66 to 9.69]) as compared with S. In terms of radical resection, CTS was more effective than S (OR = 1.73 [95% CI 1.09 to 2.76]). Findings for CTS and RTS did not differ for 5-year survival, operative mortality and postoperative complications. Conclusions: Overall, CRTS might be the best choice for resectable ESCC because it could increase the radical resection rate and lower the occurrence of complications, thereby prolonging survival time. Highlights: Esophageal squamous cell carcinoma (ESCC) accounts for most cases of esophageal carcinoma worldwide. Evidence from randomized controlled trials (RCTs) for improved effects of neoadjuvant therapy is inconsistent. Traditional meta-analysis cannot integrate all the evidence from different therapeutic methods at the same time. A network meta-analysis was used to simultaneously combine both direct and indirect evidence from RCTs for ESCC.